2020
DOI: 10.1101/2020.04.07.026047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor Promotes Differentiation During Mouse Preimplantational Embryo Development

Abstract: Mammalian embryogenesis is a complex process controlled by transcription factors that dynamically regulate the balance between pluripotency and differentiation. Transcription factor AhR is known to regulate Oct4/Pou5f1 and Nanog, both essential genes in pluripotency, stemness and early embryo development. Yet, the molecular mechanisms controlling Oct4/Pou5f1 and Nanog during embryo development remain largely unidentified. Here, we show that AhR is required for proper embryo differentiation by regulating plurip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We have shown that Ahr is required to adjust liver regeneration after acute toxic injury 22 and we and others have reported that Ahr serves to reduce hepatocarcinogenesis burden caused by postnatal exposure to diethylnetrosamine in mice 22,41 . Moreover, previous work also suggest that the higher regenerative potential and increased susceptibility to carcinogenesis of Ahr-null mice could be due to their more undifferentiated and pluripotent phenotype in different organs including liver 21,22,30,[42][43][44][45] . In this study, we have investigated potential mechanisms through which Ahr adjusts liver regeneration in response to a massive tissue removal resembling that used in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that Ahr is required to adjust liver regeneration after acute toxic injury 22 and we and others have reported that Ahr serves to reduce hepatocarcinogenesis burden caused by postnatal exposure to diethylnetrosamine in mice 22,41 . Moreover, previous work also suggest that the higher regenerative potential and increased susceptibility to carcinogenesis of Ahr-null mice could be due to their more undifferentiated and pluripotent phenotype in different organs including liver 21,22,30,[42][43][44][45] . In this study, we have investigated potential mechanisms through which Ahr adjusts liver regeneration in response to a massive tissue removal resembling that used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription was done using random priming and the iScript Reverse Transcription Super Mix (Bio-Rad). Real-time PCR (qPCR) was performed using SYBR ® Select Master Mix (Life Technologies) in a Step One Thermal Cycler (Applied Biosystems) as indicated 42,43 . Gapdh was used to normalize target gene expression (ΔCt) and 2 −ΔΔCt to calculate changes in mRNA levels with respect to untreated control conditions.…”
Section: Reverse Transcription and Real-time Pcrmentioning
confidence: 99%